Pengaruh Reputasi Perusahaan, Fluktuasi Harga Emas, Kualitas Pelayanan Dan Literasi Keuangan Terhadap Minat Nasabah Berinvestasi Melalui Cicil Emas Di PT. Pegadaian (Persero) Cabang Masbagik - Uswah, Nurul; Fitriyah, Nur; Lenap, Indria Puspitasari (Jurnal Riset Mahasiswa Akuntansi, 2024)
This study aims to determine the influence of Company Reputation, Gold Price Fluctuations, Service Quality and Financial Literacy on Customer Interest in Investing through Gold Installments at PT. Masbagik Branch Pawnshop. The type of research used is associative with a quantitative approach. The sample in this study was 100 respondents. The sampling method used in this study is probability sampling with a simple random sampling method. The data obtained were analyzed using the Structural Equation Model Partial Least Square (SEM-PLS) analysis technique through SmartPLS software version 4. The results of this study show that the Company's Reputation and Gold Price Fluctuations have a positive and significant effect on Customer Interest in Investing through Gold Installments. Meanwhile, Service Quality and Financial Literacy do not affect customer interest in investing through gold installments.